The Implementation of Problem Based Learning (PBL) Model toward Students’ Learning Outcomes in the Class XI IPA on Colloid Material at SMA Negeri 9 Palu - Almaidah Almaidah; Paulus H. Abram; Anang W. M. Diah (Universitas Tadulako, 2019)
Problem-based learning (PBL) is a learning model where students learn through practical problems related to the real life. The students conducted to solve the problems solving being discussed through a series of learning systematically. This study aimed to improve the learning outcomes of students in the class XI IPA through the implementation of PBL model on colloid material at SMA Negeri 9 Palu. This study was pre-experimental research with one group pretest-posttest design. This study was conducted by using one group observed at the pretest stage and then continued with posttest to the students of class XI IPA 1 as experiment 1 (n = 26) and students of class XI IPA 2 as experiment 2 (n = 25). The data was analyzed using descriptive statistics by calculating of N-Gain Index. The results showed that the implementation of PBL learning model improved students’ learning outcomes in the class XI IPA on colloid material at SMA Negeri 9 Palu.